Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
$-F=5x^2+4x-3=5(x^2+\frac{4}{5}x+\frac{2^2}{5^2})-\frac{19}{5}$
$=5(x-\frac{2}{5})^2-\frac{19}{5}\geq \frac{-19}{5}$ với mọi $x$
$\Rightarrow F\leq \frac{19}{5}$
Vậy $F_{\max}=\frac{19}{5}$. Giá trị này đạt tại $x-\frac{2}{5}=0\Leftrightarrow x=\frac{2}{5}$
Tìm min:
$F=3x^2+x-2=3(x^2+\frac{x}{3})-2$
$=3[x^2+\frac{x}{3}+(\frac{1}{6})^2]-\frac{25}{12}$
$=3(x+\frac{1}{6})^2-\frac{25}{12}\geq \frac{-25}{12}$
Vậy $F_{\min}=\frac{-25}{12}$. Giá trị này đạt tại $x+\frac{1}{6}=0$
$\Leftrightarrow x=\frac{-1}{6}$
Tìm min
$G=4x^2+2x-1=(2x)^2+2.2x.\frac{1}{2}+(\frac{1}{2})^2-\frac{5}{4}$
$=(2x+\frac{1}{2})^2-\frac{5}{4}\geq 0-\frac{5}{4}=\frac{-5}{4}$ (do $(2x+\frac{1}{2})^2\geq 0$ với mọi $x$)
Vậy $G_{\min}=\frac{-5}{4}$. Giá trị này đạt tại $2x+\frac{1}{2}=0$
$\Leftrightarrow x=\frac{-1}{4}$
\(A=x^2-6x-4=x^2-6x+9-13=\left(x-3\right)^2-13\ge-13\)
Vậy \(A_{min}=-13\Leftrightarrow x=3\)
\(B=x^2-x+1=x^2-2.\frac{1}{2}x+\frac{1}{4}+\frac{3}{4}=\left(x-\frac{1}{2}\right)^2+\frac{3}{4}\ge\frac{3}{4}\)
Vậy \(B_{min}=\frac{3}{4}\Leftrightarrow x=\frac{1}{2}\)
\(M=3-5x-x^2\)
\(-M=\left(x^2+2.2,5x+2,5^2\right)-9,25\)
\(-M=\left(x+2,5\right)^2-9,25\)
\(\Rightarrow M=9,25-\left(x+2,5\right)^2\)
Ta có: \(\left(x+2,5\right)^2\ge0\forall x\)
\(\Rightarrow9-\left(x+2,5\right)^2\ge9\forall x\)
\(M=9\Leftrightarrow\left(x+2,5\right)^2=0\Leftrightarrow x=-2,5\)
Vậy \(M_{m\text{ax}}=9\Leftrightarrow x=-2,5\)
\(N=-7+4x-3x^2\)
\(-N=3x^2-4x^2+7\)
\(-N=3.\left(x^2-2.\frac{2}{3}x+\frac{2^2}{3^2}\right)+\frac{17}{3}\)
\(-N=3.\left(x-\frac{2}{3}\right)^2+\frac{17}{3}\)
\(N=-3.\left(x-\frac{2}{3}\right)^2-\frac{17}{3}\)
Ta có: \(3.\left(x-\frac{2}{3}\right)^2\ge0\forall x\)
\(\Rightarrow-\frac{17}{3}-3\left(x-\frac{2}{3}\right)^2\le-\frac{17}{3}\)
\(N=-\frac{17}{3}\Leftrightarrow-3.\left(x-\frac{2}{3}\right)^2=0\Leftrightarrow x=\frac{2}{3}\)
Vậy \(N_{max}=-\frac{17}{3}\Leftrightarrow x=\frac{2}{3}\)
\(P=4-6x^2\)
Ta có: \(6x^2\ge0\forall x\)
\(\Rightarrow4-6x^2\le4\forall x\)
\(P=4\Leftrightarrow6x^2=0\Leftrightarrow x=0\)
\(P_{max}=4\Leftrightarrow x=0\)
Tham khảo nhé~